Reduced-intensity fludarabine/melphalan confers similar survival to busulfan/fludarabine myeloablative regimens for patients with acute myeloid leukemia and myelodysplasia. Issue 7 (6th June 2020) - DiMaggio, Elizabeth; Zhou, Jun-Min; Caddell, Ryan; Tombleson, Rebecca; Perkins, Janelle; Anasetti, Claudio; Khimani, Farhad; Pidala, Joseph; Nishihori, Taiga; Perez, Lia; Betts, Brian; Fernandez, Hugo F.; et al.
Abstract: Optimal conditioning chemotherapy for patients with acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS) remains uncertain. Myeloablative regimens such as fludarabine/busulfan are favored over reduced-intensity fludarabine/melphalan (Flu/Mel); however, it is not known if Flu/Mel is inferior. We analyzed hematopoietic cell transplantation recipients with AML and MDS who received fludarabine with once-daily intravenous busulfan targeted to either area under the curve (AUC) 5300 µM*L/min (Flu/Bu 5300) ( n  = 246) or AUC 3500 µM*L/min (Flu/Bu 3500) ( n  = 81), or Flu/Mel ( n  = 69). Flu/Bu regimens were compared separately to Flu/Mel. After 2-year follow-up, no differences in overall or relapse-free survival were found between Flu/Bu 5300 or 3500 versus Flu/Mel though relapse rates were significantly higher; 33.1% ( p  = 0.024), 44.6% ( p  = 0.002), versus 19.4%, respectively. Flu/Bu 5300 ( p  = 0.008) and Flu/Bu 3500 ( p  < 0.001) groups were prognostic for relapse compared to Flu/Mel. Flu/Mel yields lower relapse rates and similar survival benefit when compared to Flu/Bu 3500 or 5300 µM*L/min.